Integration of School Image Management with Character Development Programs to Improve Students' Social Adaptation - Musthofa, Zackyl; Febrianto, Febi; Rofik, Moh; Najiburrohman, Najiburrohman; Baharun, Hasan (Pendidikan Agama Islam STIT Palapa Nusantara, 2026)
This study examines how school image management is combined with character education to strengthen students' social adaptation. The research uses a qualitative case study design. Data was collected through in-depth interviews with school leaders, teachers, and students. observation of learning activities in the classroom as well as daily school routines and review of institutional documents, including vision-mission statements, rules, institutional symbols, and student programs. The data were analyzed thematically through a process of reduction, coding, and interpretation, with the reliability of the findings strengthened using triangulation of sources and methods. The results of the study show that the main character values of discipline, religious attitudes, and togetherness are at the core of the school's identity and function as common social norms that shape the pattern of student interaction. Integration becomes effective when the claimed image is consistently enacted in teaching practices, religious routines, and non-academic activities. Continuous role modeling by principals, teachers, and staff stabilizes value transmission and accelerates internalization through habituation rather than coercive control. Consequently, students develop adaptive social behavior within a coherent and predictable environment. These results imply that public relations, quality management, and school culture should be designed as an integrated system so that external reputation reflects students’ lived experiences.